Foot posture alteration and recovery following a full marathon run - Fukano, M.; Inami, T.; Nakagawa, K.; Narita, T.; Iso, S. (European Journal of Sport Science, 2018)
Prolonged running results in lowering of the foot arch and a low arch is associated with subsequent chronic injuries. Foot posture alteration and recovery following a marathon run remain unknown. Therefore, the present study aimed to evaluate foot posture alteration following a full marathon run. The three-dimensional foot posture data of 11 collegiate runners were obtained using an optical foot scanner system before, and immediately, 1 day, 3 days, and 8 days after a full marathon. The navicular height and arch height ratio significantly decreased from before to immediately, 1 day, 3 days, and 8 days after the marathon (navicular height: before, 44.2 ± 5.0 mm; immediately after, 39.4 ± 5.5 mm; 1 day, 37.7 ± 6.2 mm; 3 days, 38.7 ± 5.5 mm; 8 days, 37.6 ± 5.7 mm; arch height ratio: before, 18.4 ± 1.9; immediately after, 16.5 ± 2.5; 1 day, 15.7 ± 2.5; 3 days, 16.2 ± 2.6; 8 days, 15.6 ± 2.2, P < 0.001, respectively). By contrast, the dorsal height significantly increased from before and immediately after to 1 day after the marathon, and then significantly decreased until 8 days after the marathon (P < 0.001). These results indicate that the recovery patterns of the dorsal and navicular heights following a marathon did not coincide; the dorsal height rose temporally at 1 day after and subsequently decreased, but the navicular height decreased throughout the 8-day period after the marathon. More than one week may be necessary for sufficient foot alignment recovery from marathon-induced changes.